The response surface optimization of β-mannanase produced by Lactobacillus casei HDS-01 and its potential in juice clarification. Issue 2 (7th February 2019) - Zhao, Dan; Wang, Yao; Na, Jin; Ping, Wenxiang; Ge, Jingping
Abstract: Lactic acid bacteria (LAB) is an ideal mannanase source due to the bio-safety guarantee. LAB can heterogeneously express β -mannanase or be directly used as β -mannanase-producing strains.This research originally optimized the fermentation condition for β -mannanase produced by Lactobacillus casei HDS-01. The applicable potential of the crude enzyme in juice clarification was investigated. Two-factorial design screened out three factors, i.e., fermentation time ( p = 0.0001), glucose ( p = 0.0013), and initial pH ( p = 0.0167), which significantly affected L. casei HDS-01 β -mannanase activity. Under the predicted conditions resulting from the central composite design (CCD), i.e., fermentation time 18.23 hr, glucose 12.65 g L −1, initial pH 5.18, the model reached maximal β -mannanase activity of 81.40 U mL −1 . This model was validated by conducting six repeated experiments and subsequent t -test ( p = 0.6308). RSM optimization obtained a 1.33-fold increase in β -mannanase activity. This increase could also be qualitatively detected by larger clearance zone on konjac powder-MRS agar through Congo Red dyeing. The yield and clarity of crude β -mannanase-treated juices from orange, apple, and pear were significantly higher than controls without enzyme treatment. This study conferred a relatively high β- mannanase-producing LAB strain with a high bio-safety level and easy and economical use in juice clarification as well as other food-level fields.